2014
DOI: 10.1098/rstb.2013.0295
|View full text |Cite
|
Sign up to set email alerts
|

Widening the lens: what the manual modality reveals about language, learning and cognition

Abstract: The goal of this paper is to widen the lens on language to include the manual modality. We look first at hearing children who are acquiring language from a spoken language model and find that even before they use speech to communicate, they use gesture. Moreover, those gestures precede, and predict, the acquisition of structures in speech. We look next at deaf children whose hearing losses prevent them from using the oral modality, and whose hearing parents have not presented them with a language model in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 75 publications
(107 reference statements)
2
33
0
1
Order By: Relevance
“…A child can convey a vast variety of items in gesture by extending an index finger towards the object—a task that might be cognitively less demanding than both remembering the verbal label for an object and articulating that label as a word. There is in fact considerable evidence (see Goldin-Meadow, 2011, 2014, for recent reviews) that suggests that children convey their emerging linguistic and cognitive abilities—from first words to first explanations of various cognitive tasks involving objects—initially in gesture before they can convey them exclusively in speech, using words. As such, gesture could serve as a unique communicative vehicle in sharing information about objects at the early stages of language learning, even for children with developmental disorders.…”
Section: Discussionmentioning
confidence: 99%
“…A child can convey a vast variety of items in gesture by extending an index finger towards the object—a task that might be cognitively less demanding than both remembering the verbal label for an object and articulating that label as a word. There is in fact considerable evidence (see Goldin-Meadow, 2011, 2014, for recent reviews) that suggests that children convey their emerging linguistic and cognitive abilities—from first words to first explanations of various cognitive tasks involving objects—initially in gesture before they can convey them exclusively in speech, using words. As such, gesture could serve as a unique communicative vehicle in sharing information about objects at the early stages of language learning, even for children with developmental disorders.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the effect of timely verbal input children receive from their parents to their gestures, another likely explanation—although not mutually-exclusive— is that the act of gesturing itself might also help children take the next step in language learning, largely by reducing cognitive load (Goldin-Meadow, 2014). Even though there is very little empirical work that has tested this possibility within the domain of language development, previous work that shows close temporal contingency between the achievement of different language milestones in gesture and in speech—from first words to first explanations (for reviews see Goldin-Meadow, 2014; Özçalışkan & Hodges, 2016)—supports its likelihood.…”
Section: Discussionmentioning
confidence: 99%
“…Even though there is very little empirical work that has tested this possibility within the domain of language development, previous work that shows close temporal contingency between the achievement of different language milestones in gesture and in speech—from first words to first explanations (for reviews see Goldin-Meadow, 2014; Özçalışkan & Hodges, 2016)—supports its likelihood. On the road to mastery of different language milestones in speech, gesture offers children a cognitively easier communicative tool to practice their burgeoning knowledge of different linguistic abilities.…”
Section: Discussionmentioning
confidence: 99%
“…As an example, when teachers gesture during instruction, students retain and generalize more of what they have been taught (Goldin-Meadow, 2014). Recently, Congdon et al (2017) showed that simultaneous presentation of speech and gesture in math instruction supports generalization and retention.…”
Section: Embodimentmentioning
confidence: 99%